Predictors of pulmonary hypertension among children with atrial septal defects (ASD). Issue 1 (1st January 2022) - Chinawa, Josephat; Chinawa, Awoere T; Ossai, Edmund; Duru, Chika
ABSTRACT: Introduction: Atrial septal defect (ASD) is a common congenital heart disease in children that uncommonly presents with pulmonary hypertension. Much is not known about the exact predictor of PAH in children with ASD. Objectives: This study aimed to determine the predictors of pulmonary hypertension in children with ASD. Patients and Methods: This was a descriptive analysis of children with ASD carried out in three different institutions over a five-year period. Data entry and analysis were done using IBM Statistical Package for Social Sciences (SPSS) statistical software, version 25. Results: The majority of the participants, 52.2%, had pulmonary hypertension and 62.5% of them occurred as mild pulmonary hypertension. There was a very weak positive correlation between pulmonary hypertension and the size of atrial septal defect, increases in size of atrial septal defect correlate with increases in pulmonary hypertension and this was found not to be statistically significant (n = 67, r = 0.193, p = 0.118). There was a positive correlation between the size of atrial septal defect and the age of participants in months, increases in age correlate with increases in size of atrial septal defect and this was found to be statistically significant (n = 67, r = 0.357, p = 0.003).The highest proportion of respondents who had pulmonary hypertension, 64.7%, was seen among children less than 1 year old while the least proportion, 27.3%, was within 1–5 years, and the difference in proportions was found to be statistically significant (χ 2  = 8.187, p = 0.017). Conclusion: Pulmonary hypertension in children with ASD occur usually in the mild form. Age is the only strong predictor of PAH in children with isolated ASD.